HUBUNGAN TINGKAT KECEMASAN MAHASISWA BIDIKMISI TERHADAP PRESTASI BELAJAR - Nurcahyati Nurcahyati; Jumaini Jumaini; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Bidikmisi scholarship is an educational cost aid from the government of the Republic of Indonesia for student that has good academic potential but has economic limitation. Bidikmisi scholarship have several provisions, one of which is an IP above 3,00. These provisions can cause anxiety in bidikmisi recipient students. If this happens in the learning process, it will affect the results of their learning achievement. This study aims to determine the correlation between the level of student anxiety towards learning achievement. This research used descriptive analitic method with cross sectional approach. This research was conducted on Faculty of Teacher Training and Education also on Engineering Faculty students at the University of Riau as the sample using the cluster sampling technique. The measuring instrument used was a questionnaire developed by researchers and validity and reliability have been tested with cronbach alpha value 0,945. The analysis used was univariate analysis with frequency distribution and bivariate analysis using the Kruskall Wallis test. The results showed that 180 students (60,6%) that received bidikmisi scolarship have a moderate anxiety levels. The result of statistical tests show that there is no correlation between the level of anxiety of bidikmisi students towards learning achievement with p value= 0,450 > α (0,05). The result of this study are expected to be a source of information in the development of knowledge about the relationship between the level of anxiety of bidikmisi student towards learning achievement.Keywords: Anxiety, Bidikmisi Scholarship, Learning Achievement